The Impact of Digital-Based STEAM Learning on High School Students' Creative Thinking Skills : A Literature Review - Muhammad Ghiyats Naufal; Dwikoranto Dwikoranto; Iqbal Ainur Rizki (Journal of Digitalization in Physics Education, 2025)
Objective: This study aims to analyze the impact of STEAM (Science, Technology, Engineering, Art, and Mathematics) learning on the creative thinking abilities of high school students. With creativity being a vital skill in the 21st century, this research addresses the gap in traditional learning methods that fail to equip students with adequate creative problem-solving skills. Method: The research adopts a systematic literature review (SLR) approach involving identifying, reviewing, and synthesizing 20 articles published within the last five years. Data was collected using academic databases such as Scopus, DOAJ, and Google Scholar. The selection of articles focused on those relevant to STEAM learning and creative thinking, followed by an in-depth analysis of themes and findings.  Results:  The analysis revealed that STEAM-based learning significantly enhances creative thinking skills across various indicators, including fluency, flexibility, originality, and elaboration. Integrated models like Project-Based Learning (PjBL) and Problem-Based Learning (PBL) within STEAM provide practical strategies for overcoming traditional learning challenges by offering hands-on, practical approaches. However, limitations were identified, such as the lack of research on integrating STEAM into physics education and its limited impact on students' digital literacy.  Novelty: This study contributes to the field by highlighting the transformative potential of STEAM learning in fostering creativity, particularly when integrated with cultural and contextual elements relevant to students. It also emphasizes the importance of expanding STEAM research into less-explored areas, such as physics education and advanced digital technologies.